Pengaruh workshop kesehatan reproduksi terhadap pengetahuan pencegahan infeksi menular seksual - Citra Ayu Lestari; Asparian Asparian; Ashar Nuzulul Putra; Sri Astuti Siregar (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Reproductive health workshops are an educational method that can improve adolescents' knowledge about preventing sexually transmitted infections (STIs). Purpose: To analyze the effect of reproductive health workshops on knowledge about preventing sexually transmitted infections in eleventh-grade students. Method: This study was a quasi-experimental study with a one-group pretest-posttest design. The study population was all eleventh-grade students, with a sample of 68 respondents selected using a purposive sampling technique. Data collection was conducted using a STI prevention knowledge questionnaire, while data analysis used a paired sample t-test. Results: The average knowledge score before the workshop was 46.84 and increased to 70.59 after the intervention, representing an average increase of 23.75 points. The paired sample t-test results indicated a significant effect of reproductive health workshops on improving students' knowledge about preventing sexually transmitted infections (p-value <0.05). Conclusion: Reproductive health workshops have proven effective in improving students' knowledge about preventing sexually transmitted infections and can therefore be used as a reproductive health education strategy in schools.   Keywords: Adolescents; Knowledge; Reproductive Health Workshop; Sexually Transmitted Infections.